SHORT REVIEW OF SOME NOSQL DATABASES - Adrian RUNCEANU; Marian Ion POPESCU; Ilie BORCOSI; Dragos-Viorel IONICĂ (Fiabilitate şi Durabilitate)
The web applications we use every day use databases to store information. Thus, data have become essential for the proper functioning of daily activities. For this reason it is necessary to choose databases that satisfy the growing needs of companies nowadays. Distributed databases have emerged as the most efficient way of managing and storing data. In most cases, all users interacting with a web service or mobile application are not aware that they are interacting with a distributed database, in fact, the distributed database is implemented in the web service or mobile application offered to customers. In this article we will attempt a very brief overview of some NoSQL (Not only Structured Query Language) databases.